Analysis of Inclusive Public Service Innovation through the “DAYADINAKARA” Program at UPT RSBG Tuban - Hastri Ika Nursanti Purnamawaarti; Ika Devy Pramudiana; Ulul Albab (International Journal of Social Science and Humanity, 2026)
Inclusive public services for persons with intellectual disabilities still face various challenges, including social stigma, low public literacy, and limited access to information and social participation. In response to these problems, the Technical Implementation Unit for Social Rehabilitation of Persons with Intellectual Disabilities (UPT RSBG) Tuban developed the DAYA DINAKARA public service innovation (Support and Services for Persons with Intellectual Disabilities to Become Independent and Productive), which integrates digital approaches and social empowerment. This study aims to analyze the implementation of the DAYA DINAKARA Program in realizing inclusive public services for persons with intellectual disabilities. The study employed a descriptive qualitative approach, with data collected through in-depth interviews, observation, and document review. Data analysis was conducted using the Miles, Huberman, and Saldaña model, while the findings were interpreted using Mark H. Moore’s Public Value Theory and Ansell and Gash’s Collaborative Governance framework. The results show that DAYA DINAKARA has successfully created public value by improving public understanding, reducing social stigma, increasing beneficiaries’ independence, and strengthening the social participation of persons with intellectual disabilities. Program success is supported by institutional legitimacy, the use of digital media, family support, and multi-stakeholder collaboration. Nevertheless, the program still faces obstacles, including limited service coverage, the suboptimal development of formal collaborative forums, and the persistence of negative stigma in some communities. Therefore, strengthening institutional capacity, expanding collaborative networks, and optimizing digital media are necessary to improve the sustainability and impact of inclusive public service innovation.